Análise dos resultados maternos e neonatais associados às intervenções realizadas durante o trabalho de parto de nulíparas de baixo custo - Coelho, Tatiane da Silva (2019)
OBJECTIVE: To analyze maternal and neonatal outcomes associated with interventions performed during labor and delivery of low-risk nulliparous women. METHOD: observational, cross-sectional, descriptive and prospective study in a tertiary maternity hospital in the state of Ceará, with 534 low-risk parturients. We included: parturients who never gave birth and no maternal or fetal comorbidities. The following were excluded: parturients who became high risk during labor. Data collection was carried out from February to August 2018, in two stages: completion of a questionnaire from the observation of assistance to labor and delivery, provided by the multidisciplinary team, answered by the observer, and the search for data. in the medical records. Sociodemographic variables, obstetric antecedents, interventions in labor and delivery, maternal and neonatal outcome were considered. The research followed the ethical and legal precepts of Resolution 466/12 and was approved by CAAE 82266317.0.0000.5050. Pearson's chi-square and Fisher's exact tests were performed, 95% CI and 5% error, p <0.05. RESULTS: The sample consisted of women between 13 and 39 years old, 69.8% between 20 and 35 years old, most had a partner 51.5%, self-declared brown 63.5% and from the capital and metropolitan region of Fortaleza 91.9 %, between 6 and 10 years of study 57.5%, most without paid activity 68.3%. Obstetric background: 89.9% of women were primiparous, with gestational age between 37s and 41s4d, average of 7 prenatal consultations. Companion presence 96.4%; free liquid intake demand 78.3%; Partogram 73%; Non-pharmacological methods for pain relief 65.7% and movement during labor 75%. Interventions in labor: early admission 40.8%; Cardiotocography on admission 90.3%; venoclysis 64.8%; amniotomy 38%; At childbirth: prevalence of supine / semi-seated position 74%, encouragement of Valsalva Maneuver 72.1%; more than 4 professionals / students in childbirth 76.8%; pharmacological analgesia 8.6%. Cesarean section percentage of 39.5%. Only 31% of women received no intervention during labor, 41.2% of women received at least one intervention. For maternal outcomes, an association was observed between interventions Kristeller maneuver with postpartum hemorrhage (p = 0.036) and grade II perineal laceration (p = 0.006); Valsalva maneuver and perineal laceration (p = 0.006); non-vertical position and perineal laceration (p <0.001). For neonatal outcomes, it was observed that performing interventions during labor and delivery proved to be a “protective” factor, performing amniotomy was associated with lower oxygen demand (O2) after delivery (p = 0.001) and neonates referred to the rooming-in (p = 0.006). The use of oxytocin was associated with lower O2 requirement (0.043), Apgar score ≥ 7 in the fifth minute of life (p = 0.046) and neonates referred to the rooming-in (p = 0.027). Episiotomy was associated with lower need for O2 (p = 0.017) and newborns referred to rooming-in (p = 0.017). Valsalva maneuver was associated with lower need for positive pressure ventilation (p = 0.038), lower need for O2 (p <0.000), Apgar score ≥ 7 in the fifth minute (p = 0.047) and newborns in joint housing (p = 0.016). The prevalent expulsive period time was up to 2 hours. There was an association of incentive with Valsalva maneuver with shorter expulsive and labor analgesia with longer expulsives. It was found that the newborns were removed from skin-to-skin contact with the mother without justification such as: need for positive pressure ventilation, use of O2 and / or Apgar <7 in the 5th minute. CONCLUSION: The implementation of Good Practices is a service routine. With the exception of labor analgesia, all other interventions had high frequencies. High percentage of caesarean sections. Interventions in labor and delivery may reduce expulsion time but are at increased risk for postpartum hemorrhage. For neonatal outcomes, performing interventions proved to be a “protective” factor for newborn outcomes. The prevalent expulsive period time was up to 2 hours. There was an association between incentive to Valsalva Maneuver and shorter expulsive time and association of labor analgesia with longer expulsives. Healthy newborns were removed from skin-to-skin contact even without positive pressure ventilation, use of O2 or Apgar <7 in the 5th minute.